2014
DOI: 10.1177/0954408914527917
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of thermal control system for rapid heat cycle injection molding process

Abstract: This paper studies heat transfer during rapid heat cycle injection molding process. Actually, the mold is heated and cooled with channels in which steam or water circulates. The purpose of this numerical study is to improve the design of heating/cooling system to ameliorate the quality of the polymer part and the cycle productivity. Transfers in mold, translating thermal phenomena are predicted by the finite volume method and the fractional area volume obstacle representation in cyclic transient regime. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The used heating medium was the saturated steam, which circulates in channels at T s . The channel layout was previously chosen by Hammami et al 9 to improve both part quality and process productivity. For the heating stage, the heat transfer at the interface mold/channels can be taken into account by an overall heat transfer…”
Section: Mathematical Formulation and Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The used heating medium was the saturated steam, which circulates in channels at T s . The channel layout was previously chosen by Hammami et al 9 to improve both part quality and process productivity. For the heating stage, the heat transfer at the interface mold/channels can be taken into account by an overall heat transfer…”
Section: Mathematical Formulation and Numerical Methodsmentioning
confidence: 99%
“…Although the aforementioned works have optimized the heating efficiencies and the part quality, they have only been interested in the first heating and still have many problems to be applied in the regular RHCM cycle. Recently, Hammami et al 9 studied a 3D thermal regulation system of RHCM producing LCD panel and found a large difference between the first cycle and the regular cycle. They 9 revealed that the necessary time and the consumed energy for a heating phase can be reduced by about 50% after the first cycle molding, which has been explained by the thermal inertia of the mold.…”
Section: Introductionmentioning
confidence: 99%
“…For heating the mold to over 100 °C, electronic heaters were inserted into the volume of mold plate [ 6 ]. After that, the sheet heater was suggested for locally heating the mold surface.…”
Section: Introductionmentioning
confidence: 99%
“…They [13] have demonstrated an improvement of 27.3% in the heating efficiency when changing the original design by the optimal configuration. More recently, Hammami et al [14] and Kria et al [15] have demonstrated, through 3D numerical thermal regulation studies of RHCM molds, the necessity of carrying out simulations of several heating/cooling cycles until reaching the regular regime since they have found a strong difference between the first cycle and the regular one. They [14][15] have shown that since the second heating/cooling cycle the regular regime is reached.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Hammami et al [14] and Kria et al [15] have demonstrated, through 3D numerical thermal regulation studies of RHCM molds, the necessity of carrying out simulations of several heating/cooling cycles until reaching the regular regime since they have found a strong difference between the first cycle and the regular one. They [14][15] have shown that since the second heating/cooling cycle the regular regime is reached. Kria et al [15] have further developed the thermal regulation system of complex shaped part and have [15] proposed a "new conformal design" of heating/cooling channels combining simple horizontal drillings with concentric vertical tubes.…”
Section: Introductionmentioning
confidence: 99%